Surface Strategy Taxonomy of Language Errors in Students’ Observation Report Texts - Asmaul Husna Cantika Wiradika; Nani Solihati (Universitas Negeri Semarang, 2025)
This study analyzes language errors within the surface strategy taxonomy found in observation report texts written by tenth-grade students of class X.2 at SMAN 6 Tambun Selatan. Employing a qualitative descriptive approach, the data were collected from writing assignments completed by 32 students as representative samples. The focus of this study is to identify four types of errors based on Tarigan’s theory (2021): omission, addition, misformation, and misordering. The results of the analysis reveal a total of 26 identified errors. These findings consist of 8 omission errors, 12 addition errors, 3 misformation errors, and 3 misordering errors. The most dominant type of error is addition, with 12 instances. This indicates that students tend to use words excessively or redundantly, which results in sentences that are less coherent and less efficient. Overall, this study describes how students’ limited understanding of linguistic rules affects the quality of their factual writing in composing observation reports.